2019
DOI: 10.15625/2525-2518/57/3/13119
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Isolated From the Flowers of Camellia Chrysantha

Abstract: Camellia chrysantha (the golden camellia, golden tea) is a species of evergreen shrub or small tree belonging to the family Theaceae. The flowers and the leaves of this plant are used as tea and drank for its health benefits. The aim of this study was to investigate the chemical constituents of the flowers of Camellia chrysantha. Five flavonoids were isolated from the flowers of Camellia chrysantha (Theaceae), including (+)-catechin (1), (-)-epicatechin (2), quercetin (3), quercetin-3-O-methyl ether (4) and ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The nucleotide difference between them ranged from 0 -0.82 %, suggesting that Camellia chrysantha from Quang Ninh is a derivative of Camellia euphlebia from Bac Giang. [29] This study demonstrated for the first time the phylogenetic tree of five endemic Golden Camellias species of Vietnam in which C. petelotii, C. tamdaoensis, and C. tienii were considered endemic to Tam Dao region, Vinh Phuc province. [30] C. flava is endemic from Cuc Phuong, Ninh Binh province, [31] C. phanii is native species of Thai Nguyen province, [32] and C. euphlebia which was found in both Vietnam and China.…”
Section: Genetic Diversity Using the Dna Barcodesmentioning
confidence: 83%
See 3 more Smart Citations
“…The nucleotide difference between them ranged from 0 -0.82 %, suggesting that Camellia chrysantha from Quang Ninh is a derivative of Camellia euphlebia from Bac Giang. [29] This study demonstrated for the first time the phylogenetic tree of five endemic Golden Camellias species of Vietnam in which C. petelotii, C. tamdaoensis, and C. tienii were considered endemic to Tam Dao region, Vinh Phuc province. [30] C. flava is endemic from Cuc Phuong, Ninh Binh province, [31] C. phanii is native species of Thai Nguyen province, [32] and C. euphlebia which was found in both Vietnam and China.…”
Section: Genetic Diversity Using the Dna Barcodesmentioning
confidence: 83%
“…successfully used three genes, including matK , rbcL , and ITS2 , to identify the relationship between Camellia euphlebia and Camellia chrysantha . The nucleotide difference between them ranged from 0–0.82 %, suggesting that Camellia chrysantha from Quang Ninh is a derivative of Camellia euphlebia from Bac Giang [29] . This study demonstrated for the first time the phylogenetic tree of five endemic Golden Camellias species of Vietnam in which C. petelotii , C. tamdaoensis , and C. tienii were considered endemic to Tam Dao region, Vinh Phuc province [30] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is indigenous to Vietnam and China. This species was discovered in Ba Che (Quang Ninh) in Vietnam [3]. Numerous trace elements, including germanium, selenium, manganese, molybdenum, vanadium, and zinc, have been identified in Camellia chrysantha.…”
Section: Introductionmentioning
confidence: 99%